Sovereignty and Human Rights: A Comparison Between Western Liberal and Chinese Marxist Traditions - Boer, Roland (Political theology, 2022)
This study offers a comparison between the “rooted universals” of Western liberal and Chinese Marxist approaches to human rights. I begin with sovereignty, which is redefined in formerly colonized countries as anti-colonial sovereignty, predicated on mutual non-interference in the affairs of other states. From here, I analyze the Western liberal tradition, which arose from a unique legal tradition and its connection with private property, leading to a restricted emphasis on civil and political rights. The Chinese Marxist tradition differs, basing itself on anti-colonial sovereignty and emphasizing the core right to socioeconomic well-being, from which flow a range of further rights. The article closes with the point that it is necessary to understand and appreciate these different traditions in a global situation.